Prevalence and pathogenicity of Entamoeba histolytica in three different regions of Pernambuco, Northeast Brazil Prevalência e patogenicidade da Entamoeba histolytica em três regiões diferentes do estado de Pernambuco, Nordeste Brasileiro - Ivanize da Silva Aca; Seiki Kobayashi; Luiz Bezerra Carvalho Jr.; Seiki Tateno; Tsutomu Takeuchi (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
Parasitological examinations were carried out on 663 individuals of three different cities of Pernambuco State, Northeastern Brazil: Recife, Palmares and Bodocó. The population from a drought area of Pernambuco State, Bodocó, was investigated for amoebiasis and compared with Recife, metropolitan city (about 1.3 million of inhabitants) and another inland community, Palmares, located inside of the sugar-cane plantation region of the State. No evidence of invasive strains of E. histolytica were found in these inhabitants, provided that the isolated zymodemes I, III, IV, VIII, IX, X, XVII and XVIII are recognized as nonpathogenic strains of E. histolytica. Furthermore, the prevalence of intestinal helminths and other protozoan infections showed that these individuals are infected by other agents responsible for diarrhoeal diseases. Exames parasitológicos foram realizados em amostras fecais de 663 indivíduos residindo em três cidades do estado de Pernambuco, Nordeste brasileiro: Recife, Palmares e Bodocó. A população de Bodocó, situada na região do semi-árido de Pernambuco, foi investigada para amebíase e comparada com a do Recife, cidade metropolitana com cerca de 1,3 milhões de habitantes, e com outra da zona de plantação de cana-de-açucar do estado, Palmares. Não foi observada evidência da presença de cêpas invasivas de E. histolytica nesses habitantes desde que aquelas isoladas das amostras fecais, com zimodomas dos tipos I, III, IV, VIII, IX, X, XVII e XVIII, são reconhecidas como não patogênicas. Ademais, a prevalência de helmintos intestinais e de infecções por protozoários mostrou que esses indivíduos são infectados por outros agentes responsáveis por quadros diarréicos.